(untitled) (Research, Society and Development, 2021)
Objective: To verify the prevalence of open bite in the medical records of preventive orthodontics at the Faculdade de Ilhéus, associating it with the individual’s psychological behavior and functional analysis. Material and methods: A cross-sectional study was carried out with 145 medical records of preventive orthodontics of the Faculdade de Ilhéus in the years 2018 and 2019. Result: The prevalence of open bite identified in the medical records of preventive orthodontics of the Faculdade de Ilhéus was 15.8%. The female gender was the majority with 55%, with 61% of cases of malocclusion. Regarding the dentition that the patient was in, 73.91% were in mixed dentition, 21.74% in primary dentition and only 4.35% in permanent dentition. In the functional analysis observed in the dental document, 40.54% were oral-nasal breathers, followed by 35.14% with interposed tongue and abnormal speech was 24.22%. Patients who had an open bite in the psychological behavior item 68.75% used pacifiers and 31.25% had the habit of digital sucking. Conclusion: The data collected in this study reinforce the significant prevalence of open bite and the close association with harmful habits and the individual’s respiratory, swallowing and phonation physiology. Explanatory measures are necessary for those responsible for the prevention of harmful habits that can cause open bite in children, if the open bite is already present, it should be interfered as soon as possible, as this way the less invasive treatment can be adopted by the orthodontist, enabling a satisfactory regression to the patient.